SOCIALIZATION OF STANDARD CALCULATION OF RECIPES AND FINANCIAL RECORDING OF MSMES DODOL TENJO BOGOR - Ayu Armielia, Adestya; Iswariyadi, Arief; Alfian, Erwin; Prawira, Oqke (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Equality of welfare in Indonesia is difficult to implement due to several factors including geographical problems, population migration, and population registration. This resulted in several other problems arising, namely limited employment. To overcome this problem, the MSME entrepreneurship program is promoted by the government. Tenjo as a village famous for dodol MSMEs has a good track record in the production and distribution of dodol products in the Bogor and Tangerang areas. Unfortunately, the MSME industry is not supported by the standardization of prescriptions and financial records which are the basis for them to be able to take care of P-IRT (Home Industry Food) licenses. With the lack of knowledge from MSME business owners on the importance of standardizing prescriptions and financial records to take care of P-IRT licenses, the service team made the socialization of recipe standard calculations and financial records for MSME actors dodol Tenjo. Business actors are enthusiastic about socialization activities and can make standard prescriptions and financial records according to the model provided by the service team for them to use in their business.